THE EFFECT OF SOCIO-ECONOMY TOWARDS CONSERVATION AT CI TANDUY WATERSHED - Dede Sugandi (Indonesian Journal of Geography, 2013)
The aims of the study are: 1) Analyzing positive effect of resident’s income towards resident’sparticipation on conserving Ci Tanduy watershed 2) Analyzing negative effect of resident’sknowledge towards resident’s participation in conserving Ci Tanduy watershed, 3) Analyzingnegative effect of land possession towards resident’s participation in conserving Ci Tanduywatershed 4) Analyzing effort to improve resident’s socio-economy which supportsmaintenance and protection effort of Ci Tanduy watershed. Study method which is used issurvey with analysis with quantitative method. Analysis technique which is used is linearRegression. Area population is Ci Tanduy Watershed. Resident population is farmers andfishermen around the wwatershed. Analysis conclusion shows that 1) There is positive effectof income towards participation, 2) There is negative effect of knowledge towardsparticipation, 3) There is negative effect of land possession toward participation, 4) Areaphysical condition, which affects erosion and participation, requires resident participation.